2016
DOI: 10.1038/ncomms11073
|View full text |Cite
|
Sign up to set email alerts
|

Challenging nickel-catalysed amine arylations enabled by tailored ancillary ligand design

Abstract: Palladium-catalysed C(sp 2 )-N cross-coupling (that is, Buchwald-Hartwig amination) is employed widely in synthetic chemistry, including in the pharmaceutical industry, for the synthesis of (hetero)aniline derivatives. However, the cost and relative scarcity of palladium provides motivation for the development of alternative, more Earth-abundant catalysts for such transformations. Here we disclose an operationally simple and air-stable ligand/nickel(II) pre-catalyst that accommodates the broadest combination o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
162
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 158 publications
(162 citation statements)
references
References 65 publications
0
162
0
Order By: Relevance
“…Next, we established the direct conversion of 3G to aniline derivatives (Fig. 6c) through homogeneous nickel-catalysed crosscoupling 34,35 using a variety of amines and pseudohalogenide 8 that was obtained from 3G. Gratifyingly, 8 underwent cross-coupling with a number of amines to yield the corresponding aromatic products 9a-9e.…”
Section: Nature Catalysismentioning
confidence: 99%
“…Next, we established the direct conversion of 3G to aniline derivatives (Fig. 6c) through homogeneous nickel-catalysed crosscoupling 34,35 using a variety of amines and pseudohalogenide 8 that was obtained from 3G. Gratifyingly, 8 underwent cross-coupling with a number of amines to yield the corresponding aromatic products 9a-9e.…”
Section: Nature Catalysismentioning
confidence: 99%
“…Additionally, it has been demonstrated that this class of precatalyst is compatible with sterically bulky ligands that stabilize highly active cross-coupling catalysts, such as PAd-DalPhos (REF. 141), whereas most Ni precatalysts have only been used with more traditional monophosphines such as PPh 3 or PCy 3 . Activation of precatalysts of the type [L n Ni(Ar)X] generally involves transmetallation of the halo ligand with the nucleophile in cross-coupling followed by reductive elimination 140,142,143 .…”
Section: Ni-based Precatalystsmentioning
confidence: 99%
“…For example, even low loadings of [(dppf)Ni( o -tolyl)Cl] enable coupling of heteroaryl chlorides and aryl sulfamates with boronic acids at ambient temperatures 140,142 . Additionally, when ligated with the bidentate phosphines PAd-DalPhos 141 or dppf 137 , this precatalyst system can mediate the Buchwald–Hartwig amination of heteroaryl halides and pseudohalides. In fact, [(PAd-DalPhos)Ni( o -tolyl)Cl] generates an active catalyst that allows the use of ammonia as the nucleophile in such reactions and is an example of the use of this precatalyst class with some of the most recently developed ligands for cross-coupling.…”
Section: Ni-based Precatalystsmentioning
confidence: 99%
“…Moreover, the catalytic activities using gold complexes with selone ligands are better than those of gold complexes with thione ligands [38] and HAuCl 4 . Then, the complex 3 was chosen as the optimal catalyst to screen the various solvents (Table 3, entries [8][9][10][11][12]. High yield of 95% of the desired products was achieved within 3 h in water solvent.…”
Section: Catalytic Reduction Of Nitroarenesmentioning
confidence: 99%
“…Therefore, a variety of protocols for synthesizing functionalized anilines have been developed [7][8][9][10][11][12][13][14][15][16][17][18][19]. The desirable method for the synthesis of functionalized anilines is the reduction of nitroarenes using transition metal catalysts in the presence of sodium tetrahydroborate (NaBH 4 ) [20].…”
Section: Introductionmentioning
confidence: 99%